Transformation of Foreign Policy in Bulgaria in the Context of Internal and External Factors in the Postcommunist Era - IŞIK, Mustafa (CenRaPS Journal of Social Sciences, 2023)
Radical changes in world politics after the Cold War led to structural changes in the foreign policies of states. This change and transformation process is not only systemic, but also reflected in the state and leader profiles. Our study aiming to explain the changes in Bulgarian foreign policy in the postcommunist process; uses Neoclassical Realism as a theoretical framework. While the communist regimes in Eastern Europe and the Balkans were collapsing in an environment where the balance of power was changed by the trigger of the systemic effect, this power vacuum led the former Eastern Bloc countries to seek new foreign policies. This process brought about a rapprochement with the Euro-Atlantic structure in the Balkan countries. In this context, our main research question is; How can we explain the pro-Euro-Atlantic foreign policy of Bulgaria, a former Eastern Bloc country, after the Cold War? How did intra-state factors and leaders affect the transformation process of foreign policy? In the postcommunist period, there were great changes in Bulgaria's domestic and foreign policy. While new leader profiles emerged in domestic politics, pro-EU and NATO political formations were included in the political arena. In this process of change, the Turkish and Muslim minorities assumed important roles in the political system and supported pro-EU and NATO policies. In this process, although the Bulgarian Communist Party tried to carry out the representative policies of the past, it could not resist the changes in domestic and foreign policy. Political parties founded by minorities and new political formations advocating European integration have been one of the main dynamics of change at the intra-state level. In this context, the impact of the Turkish and Muslim minority on foreign policy will also be evaluated within the scope of the research. Neoclassical realism takes into account the power changes within the international system, but also includes intra-state factors in the analysis. Neoclassical realist theory, which gives the opportunity to deal with the change in Bulgaria in a multidimensional way, also opens an important area for the leaders. Neoclassical realism deepens foreign policy analysis because it deals with internal and external factors together. It is seen that neoclassical realism offers a more systemic and comprehensive analysis framework by including internal factors in the analysis at the point of explaining the changes in foreign policy.